Pelatihan Digital Marketing Dan Sertifikasi Halal Terhadap Masyarakat Gunung Manik - Arif Widodo Nugroho; Elmy Nur Azizah; Dewi Pudji Rahayu; Della Pariska; Lailatul Salamah; Fikri Hidayat (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
This service activity is carried out for the community in Gunung Manik which is aimed at achieving an increase in income and public understanding in digital marketing. The participants who participated in this activity amounted to 30 people, of which they were business actors. However, there are also some residents who do not have a business, but have the desire to be entrepreneurial. This service activity is carried out using the lecture and discussion method. The series of activities consists of several stages, namely planning, preparation and implementation Digital marketing techniques are provided by utilizing technology available today. That way, maximizing marketing of business products owned by the community will be easier to do. Meanwhile, the introduction of halal certification is carried out by bringing in experts directly.